PENGARUH EXPRESSIVE WRITING THERAPY TERHADAP KECEMASAN IBU POST PARTUM DI PUSKESMAS KECAMATAN KRAMAT JATI - Savira Ilsa Fahrina (2021)
Anxiety is a feeling that cannot be expressed in words but can be seen from various body gestures. Postpartum mothers who experience anxiety will look helpless and feel anxious for no apparent reason. The cause of anxiety is a feeling of guilt as a result of an action that someone does which turns out to be something unexpected. Other than that, the fear of bad things that happen to oneself can also cause a person to feel anxious. As many as 18-70% of postpartum mothers in Indonesia experience anxiety. This number is higher from the World Health Organization (WHO), which revealed that the prevalence of postpartum maternal anxiety in the world is 3.6%. Postpartum anxiety in mothers can be reduced by doing expressive writing therapy. This research aims to determine the effect of expressive writing therapy on maternal anxiety postpartum. The pre-experimental design technique with One-Group Pretest-Posttest Design (without control) was used to conduct this research, with a sample of 30 respondents using the accidental sampling technique. The result shows that there is an effect of expressive writing therapy on the anxiety of postpartum mothers with a p-value of 0.000 < 0.05. The average of postpartum anxiety before the therapy was 14.67. Meanwhile, the average postpartum anxiety after therapy is 10.97.